Identification and resistance profile of pathogenic bacteria in Nile tilapia (Oreochromis niloticus) againts antibiotics in the waters of the Meureubo River, West Aceh District - M. Barru Airil Fizra Hasibuan; Irhami S.; Khairul Samuki; Alfis Syahril (Acta Aquatica: Aquatic Sciences Journal, 2026)
This study aimed to identify pathogenic bacterial species and analyze their antibiotic resistance profiles in Nile tilapia (Oreochromis niloticus) collected from the Meureubo River, West Aceh Regency. The research was conducted through several stages, including fish sampling, bacterial isolation, and culturing on Nutrient Agar, Tryptic Soy Agar, and MacConkey Agar media, followed by Gram staining, biochemical characterization, and antibiotic susceptibility testing using the Kirby–Bauer disk diffusion method. The results indicated significant water quality degradation at the midstream (L2) and downstream (L3) stations, characterized by decreased dissolved oxygen (DO) and increased ammonia levels. From fish samples exhibiting clinical symptoms (ulceration, fin rot, hepatomegaly), five major bacterial genera were isolated: Aeromonas hydrophila, Streptococcus agalactiae, Edwardsiella tarda, Flavobacterium columnare, and Pseudomonas spp. Antibiotic resistance testing revealed that amoxicillin (AMX) and erythromycin (ERY) showed the highest resistance levels among the isolates, whereas enrofloxacin (ENR) and kanamycin (KAN) remained highly effective. The Multiple Antibiotic Resistance (MAR) index values ranged from 0.0 to 0.4, with Edwardsiella tarda and Flavobacterium columnare classified as multidrug-resistant. These findings confirm that increasing anthropogenic activities around the Meureubo River contribute to the emergence of pathogenic bacteria and antibiotic resistance. Overall, this research provides essential scientific insights for managing tilapia health and controlling antimicrobial resistance in public freshwater ecosystems. Keywords: Antibiotic Resistance; Meureubo River; MAR index; Oreochromis niloticus; Pathogenic Bacteria